If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (9x + 24) + (6x + 6) = 0 Reorder the terms: (24 + 9x) + (6x + 6) = 0 Remove parenthesis around (24 + 9x) 24 + 9x + (6x + 6) = 0 Reorder the terms: 24 + 9x + (6 + 6x) = 0 Remove parenthesis around (6 + 6x) 24 + 9x + 6 + 6x = 0 Reorder the terms: 24 + 6 + 9x + 6x = 0 Combine like terms: 24 + 6 = 30 30 + 9x + 6x = 0 Combine like terms: 9x + 6x = 15x 30 + 15x = 0 Solving 30 + 15x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 15x = 0 + -30 Combine like terms: 30 + -30 = 0 0 + 15x = 0 + -30 15x = 0 + -30 Combine like terms: 0 + -30 = -30 15x = -30 Divide each side by '15'. x = -2 Simplifying x = -2
| -3x-2y+12=0 | | (4x+17)+28=6x | | 5+n=8n+5-4n | | 1.4z-5=3.7 | | 9(k-10)=k | | (x+3)2=36 | | 7p-1=-15 | | 5.3x-8.1=23.7 | | 900x=400+100x | | F(x)=3x+9Findf(2c-4) | | -8n+7n=-n | | 14x/15=7/30 | | 288*.30=x | | 3v-1+2+16=5+5v+4 | | X*.30=86.50 | | 3x-20=2x+2 | | 2(2x+1)-x=11 | | 12=2/3x-4 | | 2(5-3x)=3(4x+1) | | 12+5b=-2b-5b | | -top-4=to | | F(1)=3x^2-7 | | 3x+6y+1=10 | | 9f^2+f=0 | | 9u=3 | | 1.4(2.5x-2.8y)-3.5(2.0x+1.5y)= | | 1-5x=1-3x-3x | | -6p^2-2p+9=0 | | Z=4c/n | | a-45=20 | | 3x+46=-13x-6-10x | | (5/6)b=1(7/8) |